1998
DOI: 10.1136/ip.4.2.106
|View full text |Cite
|
Sign up to set email alerts
|

Rates of, and the factors affecting, cycle helmet use among secondary schoolchildren in East Sussex and Kent

Abstract: Objectives-To assess the level of cycle helmet wearing among young people in two counties in the South East of England in 1994, and to identify the factors associated with helmet wearing. Design-Cross sectional survey in a convenience sample. Setting-Secondary schools in East Sussex and Kent. Subjects-Students in year 7 (aged 10-12 years) and year 11 (aged 14-16 years). Main outcome measures-Self reported "always wears a helmet". Results-Among those who ride a bicycle, 32% of boys and 29% of girls aged 10-12 y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
12
2

Year Published

2002
2002
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 28 publications
3
12
2
Order By: Relevance
“…The findings of this study showed that self-reported bicycle helmet use was alarmingly low (4.4%) among children at a predominantly low and mid-income school. This rate was lower than in several international studies, despite the rates of helmet wearing by bicycle riders being lower than desirable in International Journal of Injury Control and Safety Promotion 371 these studies also (Bernstein, Harper, Pardi, & Christopher, 2003;Clements, 2005;Coffman, 2003;Cryer et al, 1998;Fischer et al, 2012;Forjuoh, Fiesinger, Schuchmann, & Mason, 2002;Kakefuda et al, 2009;Karkhaneh et al, 2006;Karkhaneh et al, 2011;Khambalia et al, 2005;Klein et al, 2005;Lee et al, 2009;O'Callaghan & Nausbaum, 2006;Page et al, 2012;Ross et al, 2011). Several factors may explain this low rate of helmet use among 8-16 year old Turkish children.…”
Section: Discussioncontrasting
confidence: 58%
See 1 more Smart Citation
“…The findings of this study showed that self-reported bicycle helmet use was alarmingly low (4.4%) among children at a predominantly low and mid-income school. This rate was lower than in several international studies, despite the rates of helmet wearing by bicycle riders being lower than desirable in International Journal of Injury Control and Safety Promotion 371 these studies also (Bernstein, Harper, Pardi, & Christopher, 2003;Clements, 2005;Coffman, 2003;Cryer et al, 1998;Fischer et al, 2012;Forjuoh, Fiesinger, Schuchmann, & Mason, 2002;Kakefuda et al, 2009;Karkhaneh et al, 2006;Karkhaneh et al, 2011;Khambalia et al, 2005;Klein et al, 2005;Lee et al, 2009;O'Callaghan & Nausbaum, 2006;Page et al, 2012;Ross et al, 2011). Several factors may explain this low rate of helmet use among 8-16 year old Turkish children.…”
Section: Discussioncontrasting
confidence: 58%
“…Several studies have reported that factors, such as bicycle helmet laws, age, gender, race, income, level of education among household members, environment, role modelling, parental education, perception of the risks of bicycle-related head injuries by the child and parent, and knowledge about bicycle safety are associated with bicycle helmet use (Berg & Westerling, 2001;Cryer et al, 1998;Davis, Kirsch, & Pullen, 2003;Dellinger & Kresnow, 2010;Klein et al, 2005;Loubeau, 2000;O'Callaghan & Nausbaum, 2006;Ross et al, 2011). Understanding the factors that predict helmet use is essential for encouraging helmet use.…”
Section: Introductionmentioning
confidence: 97%
“…The first found 30% of 11 year olds reported always wearing a helmet, 3 very similar to our findings. The second study found that 64% of helmet owners reported wearing them always or nearly always, 16 higher than that found in our study.…”
Section: Principal Findingssupporting
confidence: 81%
“…How this study compares to other studies Two previous UK surveys in children of a similar age to our study population found helmet ownership rates of 69% in East Sussex 3 and 58% in South Staffordshire, 16 higher than the 52% found in our study. The first found 30% of 11 year olds reported always wearing a helmet, 3 very similar to our findings.…”
Section: Principal Findingscontrasting
confidence: 61%
“…Previous research has identified numerous factors related to helmet use among adolescents, including past helmet use behavior (Quine, Rutter, & Arnold, 1998;Seijts, Kok, Bouter, & Klip, 1995), role modeling, parental encouragement, (Cryer et al, 1998;Lajunen & Rasanen, 2001), attitudes (Berg & Westerling, 2001;Cryer et al, 1998;Rodgers, 2000), and having friends who use helmets (Cryer et al, 1998;Lajunen & Rasanen, 2001). Furthermore, safety considerations (Berg & Westerling, 2001;Finch, 1996), compulsory helmet wearing by law (Sutton, 1994), and educational campaigns (Ashby, Routley, & Stathakis, 1998;Brewer et al, 1995) have been associated with increased use of helmets.…”
Section: Introductionmentioning
confidence: 94%